Avoidance of Routine Use of Episiotomy in Primigravida - Hamda, Trifa Ahmed; Alsakkal, Ghada S. (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: The justification of the routine use of the episiotomy arouse at the beginning of 20th century. It was based on personal beliefs without scientific basis and this led to the incorporation of episiotomy in daily practice . High-quality methodological studies gave strong evidence that episiotomy should not be done routinely. The purpose of this study was to find out the rate and degrees of perineal tear in women with versus without episiotomy and to evaluate the severity of pain and complications including wound infection, wound dehiscence and dyspareunia. Methods: This is a prospective interventional study included 200 primigravida with term pregnancy, who attended the labor room at Maternity Teaching Hospital from 1st of January 2008 till 1st of July 2008. Episiotomy was done for a group and avoided in another group, then follow up was done to evaluate complications. Results: Perineal tears were significantly more in patients with episiotomy as episiotomy itself is regarded as second degree perineal tear. There was significant difference in the severity of pain, wound infection and dyspareunia among both groups but there was no significant difference in the Apgar score of the newborn in both group. Conclusion: This study does not supports maternal benefits of routine episiotomy.